Relationship Between Adversity Quotient And Answering Between The Tahfidz Exam At The Santri Pondok Pesantren: Hubungan Antara Adversity Quotient Dengan Kecemasan Menjelang Ujian Tahfidz Pada Santri Pondok Pesantren - Esti Annisa Nurfitri; Dwi Nastiti (Academia Open, 2022)
Show students before the tahfidz exam. The purpose of this study is to determine the relationship between adversity quotient and anxiety before the tahfidz exam in students at the Darul Fikri Islamic Boarding School, Sidoarjo. The research method is a correlational quantitative method. The research sample was 66 students obtained by saturated sampling. The data collection method uses 2 psychological scales, namely the Adversity Quotient scale and the Anxiety Scale Ahead of the Tahfidz Exam. The proposed hypothesis is that there is a significant negative relationship between adversity quotient and anxiety before the Tahfidz exam. The result, r = -0.232, p = 0.030 (p < 0.05), which means the research hypothesis is accepted. The higher the adversity quotient, the lower the anxiety before the tahfidz exam. On the other hand, the lower the adversity quotient, the higher the anxiety before the tahfidz exam in students at the Darul Fikri Islamic Boarding School. Keywords: adversity quotient, anxiety, tahfidz exam, santri